On the margins : Jews and Muslims in interwar Berlin - Jonker, Gerdien, (Muslim Minorities;, 2020)
"This study addresses encounters between Jews and Muslims in interwar Berlin. Living on the margins of German society, the two groups sometimes used that position to fuse visions and their personal lives. German politics set the switches for their meeting, while the urban setting of Western Berlin offered a unique contact zone. Although the meeting was largely accidental, Muslim Indian missions served as a crystallization point. Five case studies approach the protagonists and their network from a variety of perspectives. Stories surfaced testifying the multiple aid Muslims gave to Jews during Nazi persecution. Using archival materials that have not been accessed before, the study opens up a novel view on Muslims and Jews in the 20th century".